Impact Of Extensive Reading On Ecuadorian Learners' Attitudes Toward L2 Reading: A Qualitative Research Study. - Salvador Cisneros, Katherine Anabelle (2016)
Globalization trends have pushed ecuadorians into the need to read texts in foreign languages such as english. People in ecuador need to read english texts for many different purposes in business, academic and social contexts. in addition, ecuadorian business people need to be able to read in english in order to better understand legally binding commercial documents which facilitate international relationships. many people from other places where spanish is not spoken visit ecuador, so speaking and reading english texts become a way to interact with these people as tourists and in social situations. Academic reading in english is also necessary for ecuadorians, who seek to improve their english for professional reasons. these ecuadorian language learners attend english language centers or take private classes.